High-resolution integrated stratigraphy of Upper Ordovician to lower Silurian strata: applications to black shale drill cores in South China - Sun, Zongyuan; Melchin, Michael J.; Storch, Petr; Chen, Qing; Zhao, Fangqi; Fan, Junxuan (Newsletters on Stratigraphy, 2024)
This paper presents an integrated stratigraphy of the Upper Ordovician to lower Silurian strata from the Yangtze platform, focusing on detailed graptolite biostratigraphy and 8 13 C org chemostratigraphy of a continuous drill core section. We establish ten graptolite biozones within the Wufeng and Lungmachi forma- tions and identify the LKCIE (Late Katian Carbon Isotope Excursion), HICE (Hirnantian Isotope Carbon Excursion), and EACIE (Early Aeronian Carbon Isotope Excursion) in the 8 13 C org curve. Through the identi- fication of four positive carbon isotope excursions, including the LACIE (Late Aeronian Carbon Isotope Excursion), this paper addresses and clarifies the substantial uncertainties in biozonal boundaries identified in previous research, providing a definitive integrated stratigraphy framework, and significantly enhances both regional and global stratigraphic correlation. Our approach revises biozone boundaries within drill cores and outcrop sections in South China, revealing abrupt turning points in depositional rate changes within the Lungmachi Formation, linked to the Kwangsian Orogeny and global sea-level fluctuations. This high-resolu- tion stratigraphic framework contributes to biostratigraphy and chemostratigraphy and aids in efficient hy- drocarbon